(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the clinical lab diagnostic accuracy for renal failure and rhabdomyolysis due to paraphenylene-diamine (PPD). Study Design: Non-experimental cross-sectional study Place and Duration of Study: This study was conducted at the Department of Forensic Medicine, Foundation University Medical College, Islamabad from Jan-Dec 2018. Materials and Methods: Data was analyzed on SPSS version 20. Chi-square test was applied for the analysis of qualitative variables. Two tail tests were applied for quantitative variables. Frequencies with percentages mean with standard deviation and median with inter-quartile range was given for quantitative data. P-value < 0.05 was considered significant. Exclusion criteria include patient with mixed disease history or having medical co-morbidities were excluded from this study Results: In the present study, 658 cases of Kala Pathar poisoning were diagnosed and treated. M: F ratio is 5:20. There were 518 (78.8%) females and 139 (21.2%) males. Majority of the female patients were married 488 (78.0%). Most common clinical manifestations include marked facial edema; dysphagia and stridor. Post complications include Rhabdomyolysis and acute renal failure which develop after two to five days. Initial lab investigations within 6-8 hours after ingestion showed marked increase in TLC count, SGPT and Na+ ions. There is decrease in K+ & HCO3 ions. There is marked elevation of serum creatinine kinese (CK) after 24 hours. Conclusion: ‘PPD poisoning is more common in females of younger age group belonging to rural areas. Early diagnosis and prompt supportive treatment can save many lives. There is no specific antidote available.